2000
DOI: 10.1038/sj.onc.1203872
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of proliferation-survival decisions is controlled by FGF1 secretion in retinal pigmented epithelial cells

Abstract: Fibroblast growth factor 1 (FGF1) induces proliferation and dierentiation in a wide variety of cells of mesodermal and neuroectodermal origin. FGF1 has nò classical' signal sequence to direct its secretion, and there has been considerable debate concerning FGF1 secretion and its role in the biological activities of FGF1. We investigated the eects of FGF1 secretion and the signalling induced by signal peptide (SP)-containing FGF1 and SP-less FGF1, on the proliferation and the apoptosis in retinal pigmented epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 68 publications
2
11
0
Order By: Relevance
“…However, both positive and negative regulating effects on cell proliferation have been demonstrated for the MAP kinase pathway. It has recently been shown that ERK1/2 transmits anti-apoptotic signals in serumdepleted RPE cell cultures (Guillonneau et al, 1998;Bryckaert et al, 2000). In this study, we demonstrate that ERK2 also controls cell proliferation in serumstimulated RPE cell cultures, suggesting that ERK2 may control different cell fate, proliferation and survival, in the same cell type.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…However, both positive and negative regulating effects on cell proliferation have been demonstrated for the MAP kinase pathway. It has recently been shown that ERK1/2 transmits anti-apoptotic signals in serumdepleted RPE cell cultures (Guillonneau et al, 1998;Bryckaert et al, 2000). In this study, we demonstrate that ERK2 also controls cell proliferation in serumstimulated RPE cell cultures, suggesting that ERK2 may control different cell fate, proliferation and survival, in the same cell type.…”
Section: Discussionsupporting
confidence: 49%
“…Nothing is known about the signalling and the molecular mechanisms underlying these processes and we still know very little about the intracellular signalling that mediates RPE cell proliferation. ERK1/2 was recently reported to be involved in RPE proliferation stimulated by fibroblast growth factors, but no upstream or downstream activators of the ERK pathway were analysed (Bryckaert et al, 2000). It would therefore be useful to determine precisely which signalling pathways mediate serum-stimulated RPE cell proliferation, to make it possible to inhibit this process specifically in RPE diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this finding, several proteins lacking a signal sequence in bacteria and yeast are secreted through an alternative secretory machinery such as ATP binding cassette transporters (Kuchler, 1993). Accumulating evidence also suggests that eukaryotic cells secrete proteins lacking signal peptides, including interleukins (MacKenzie et al, 2001), fibroblast growth factors (Bryckaert et al, 2000), annexin II ( Siever and Erickson, 1997), and galectins (Barondes et al, 1994). These proteins are extracellularly translocated by the alternative secretory pathways, which may also involve ATP binding cassette transporters (Lottaz et al, 2001).…”
Section: Proteomic Analysis Of Secreted Proteinsmentioning
confidence: 54%
“…The onset mechanism of proliferation in mitotically quiescent RPE cells is not fully understood in either humans or newts, although it can be a clinical target for manipulating both retinal diseases and regeneration. To address this issue, plenty studies have been conducted thus far using primary cultures of isolated RPE cells or cell lines established from those cells (Bryckaert et al., 2000; Hecquet et al., 2002a,b; Hollborn et al., 2006; Kaven et al., 2000; Lashkari et al., 1999; Pacheco‐Domínguez et al., 2008; Palma‐Nicolas et al., 2008; Parrales et al., 2010; Susaki and Chiba, 2007). However, these systems might not be suitable because isolated cells have already received some signals to become mitotically active during the enzymatic dissociation process.…”
Section: Introductionmentioning
confidence: 99%